Grandivittin as a natural minor groove binder extracted from Ferulago macrocarpa to ct-DNA, experimental and in silico analysis. (25th October 2016) - Ahmadi, F.; Valadbeigi, S.; Sajjadi, S.E.; Shokoohinia, Y.; Azizian, H.; Taheripak, G.
Abstract: Ferulago macrocarpa (Fenzl) Boiss., is an endemic medicinal herb of Iran. In this study a dihydrofuranocoumarin called grandivittin (GRA) was separate and purified from Ferulago macrocarpa (Fenzl) Boiss, and characterized by 1 H NMR and Mass spectroscopic methods. The electrochemical behavior of GRA was evaluated by cyclic voltammetry (CV). The interaction of GRA with calf thymus double strand deoxyribonucleic acid (ct-DNA), was evaluated by CV, differential pulse voltammetry (DPV), fluorescence, UV–Vis, FT-IR and molecular modeling methods. The thermodynamic parameters of GRA-DNA complex were measured and reported as: ΔH = 15.04 kJ mol −1, ΔS = 105.54 J mol −1 and ΔG = −15.62 kJ mol −1 . Docking simulation was performed to investigate the probable binding mode of GRA to various DNA, too. The polymerase extension study was performed using real-time PCR to confirm the inhibitory effect of GRA on polymerase extension activity as a mirror of binding to ct-DNA. However, all data showed that the grooves binding especially minor groove between GRA and ct-DNA is more predominant rather than other binding modes. Graphical abstract: Highlights: Grandivittin was extracted from Ferulago macrocarpa (Fenzl) Boiss. Interaction of GRA with ct-DNA, was evaluated by experimental and molecular modeling methods. The minor groove binding between GRA and ct-DNA was obtained. The polymerase extension study was performed using real-time PCR.